Automatic Car Park System Using RFID and Android Application - Muhamad Zulhairi Bin Nazar Mohd Zarizi; Lilywati Binti Bakar; Zurina Binti Abdul Wahab (Progress in Engineering Application and Technology, 2023)
With the number of vehicles on the rise and parking becoming a big burden in urban and semi-urban places, there is a need to create a parking system with updated technologies that would eliminate manual input as well as the problem of vehicles parking on roadways. The challenges related with parking are normal to most of us such as we always struggle to find a safe parking place with a minimal time taken. This research seeks to examine internationally adopted parking management techniques that employ various technology. This research also intends to investigate the shift in focus of current parking management techniques by evaluating a range of parking management solutions from across the world.